Anthropometry, physical and movement features, and repeated-sprint ability in soccer players - Campa, F.; Semprini, G.; Júdice, P. B.; Messina, G.; Toselli, S. (International Journal of Sports Medicine, 2019)
This study aimed to evaluate the associations of anthropometry, functional movement patterns (FMP) and physical performance characteristics with repeated-sprint ability (RSA) in male youth soccer players. Thirty six athletes (ages 16.6±0.5 years, BMI 22.0±1.3 kg/m2) completed the RSA test and other physical tests including countermovement jump with (CMJA) and without the help of arms (CMJ), 10-m and 20-m straight-line sprints, Yo-Yo Intermittent Recovery Test Level 1 (Yo-Yo), and functional movement screen (FMS). In addition, a battery of anthropometric variables was measured. RSA performance components such as best time (BT), mean time (MT) and sprint decrement were calculated. Results showed that measures of physical performance derived from horizontal plane in 10-m and 20-m sprints, were more strongly associated (p<0.01) with RSA performance than those obtained with CMJ or CMJA (p<0.05). High correlations (p<0.01) were found between MT, BT and Yo-Yo distance (r=-0.79, r=-0.67, respectively), as well as with FMS scores (r=-0.68, r=-0.58, respectively). Anthropometric measures, such as fat mass, upper fat area, thigh fat area, calf muscle area, and endomorphy were associated with RSA components (p<0.05). Predictors for the RSA performance identified in the stepwise multivariate analysis included Yo-Yo distance, time in sprints, FMP, and calf muscle area.